An ecotoxicologically relevant approach to water quality monitoring for contaminants of emerging concern - Schoenfuss, Heiko L.; Kolok, Alan S. (Frontiers in Water, 2023)
Contaminants of Emerging Concern (CECs) have been documented across the seven continents, including Antarctica, and are likely an impediment to the sustainable management of natural resources. Most studies to date have relied on sweeping chemistry surveys, reliant upon sophisticated instrumentation. This approach is expensive, relies on limited laboratory capacity, and generates results that are spatially and temporally constrained. Here we review existing approaches that can overcome these limitations by focusing on effects-based monitoring. Passive samplers can generate long-term records regarding the occurrence of CECs. As samples are concentrated, their analysis can be achieved using equipment that will be more common and less expensive. A second approach involves rapid test methods for single compounds, including test strips, ELISA assays, and mobile phone-based analytic tools. These can provide inexpensive CEC presence data for many field sites and can be used to stratify sampling and thereby reduce cost. Identifying the presence of a single compound can often shed light on the likely presence of entire groups of chemicals. Pairing these chemistry-derived approaches with geospatial modeling to predict CEC presence and concentrations across watersheds has already been applied in several large watersheds. Utilizing available ecotoxicological knowledge bases provides an opportunity to link modeled CEC occurrence and concentrations with likely adverse biological responses. Finally, confirmatory on-site exposure experiments can corroborate the presence or absence of biological effects hypothesized from the above chain of evidence to provide natural resource managers with information to make conservation decisions.